TRANSFORMASI Agrobakterium rhizogenese DAN INDUKSI AKAR RAMBUT PADA TANAMAN KAKAO (Theobroma cacao) UNTUK PRODUKSI SENYAWA ANTIOKSIDAN SECARA INVITRO - Syukur, Sumaryati; Aneloi N, Zozy; Putri, Femilya (Jurnal Riset Kimia, 2009)
ABSTRACT Transformation of Ri T-DNA Plasmid Agrobacterium rhizogenese to varieties Theobroma cacao variety TSH which is growing in west Sumatra and induction of hairy roots in order to produce bioflavonoid antioxidant compounds such as, catechin, polyfenol, or monomer and oligomer flavones was successfully obtained. Three spesies of A.rhizogenese (A4,LBA 9457 and ATTCC 15834) originaly from LIPI was used to transform Ri T-DNA plasmid in MS medium via cacao embryo culture. The aim of this paper is to determine the affectivity and ability of the three species of bacterial above to produce hairy roots in cacao invitro culture. The statistical methods RAL was uses with 4 time treatments and 6 time repeated experiments. As treatment was bacterial inoculation and without inoculation as a control. The transformation result shows 2 of 3 of bacterial species have ability to induce hairy roots of.T cacao embryos counting by percentages of explants with producing hairy roots 16.66% for A4, 83.33% for LBA 9547 spesies.qualitative test of polyfenol from hairy roots transformants give (+4) as compared to non transform only (+1). Cathechin compound was determined by spectrophotometer as much as 0.1% for non transform and 0.87 % for hairy roots transformants by LBA 9547. Conformation of plasmid Ri T-DNA hairy roots from two transformants was analysis by PCR methods. The two primers rol B1 (52ATGGATCCCAAATTGCTTCCCCCACGA32) dan rol B2 (53 TTAGG CTTTCATTCGGGTTTACTGCAGC 33) was used. For TR-DNA the primes used is TRI (53 GGAAATTGTGGCGTTGTTGTGGAC 3’) and  TR2 (5’ AATCGTTCAGAGAGCGTCCGA AGTT 3’) . PCR analysis of DNA electrophoresis founded the band of TL region at 780 bp and TR at 1600 bp using DNA Ledder as DNA standard.  Keywords : transformation A.rhizogenese, PCR, Theobroma cacao, kultur embrio, kultur akar rambut, metabolit sekunder, cathechin